Evaluation of the Quality and Reliability of Youtube Videos on Pelvic Pain in Pregnancy - Ulgen Kiratlioglu, Esra; Kiratlioglu, Yusuf; Uran San, Ayca (Gynecology Obstetrics & Reproductive Medicine, 2025)
OBJECTIVES: Pelvic pain in pregnancy is a problem that cannot be underestimated. A growing number of people use social media to access health-related information. Like many people, pregnant women search YouTube for guidance on pelvic pain. However, the quality of the content of YouTube videos is controversial. In this study, we aimed to evaluate the quality and reliability of medical information on videos considering pelvic pain in pregnancy shared on YouTube. STUDY DEISING: In April 2024, this cross-sectional study was carried out with a search conducted on YouTube with “pelvic pain in pregnant women” and “pelvic pain in pregnancy” as keywords. From a total of 100 videos, following review and exclusion, the remaining 55 videos’ characteristics were recorded. The video’s reliability was evaluated by the DISCERN questionnaire, quality by the Global Quality Scale, and content accuracy by The Journal of the American Medical Association Benchmark Scoring System. RESULTS: A total of 100 videos were analyzed, and 55 were included. Regarding the video sources, 12 were uploaded by physicians, 23 by non-physician healthcare professionals, and 20 by nonprofessionals (fitness trainers, pilates instructors, influencers, and patients sharing their personal experiences). There were no significant differences (p>0.05) among video sources in terms of descriptive characteristics. Among all analyzed videos, only those uploaded by physicians and non-physician healthcare professionals were of high quality, accounting for 22% of the total. There was a positive correlation between the DISCERN questionnaire, The Journal of the American Medical Association Score, and Global Quality Scale scores. All three of these scores were significantly higher in the videos uploaded by physicians and non-physician healthcare professionals than those in the nonprofessional group. CONCLUSION: On the whole, the majority of videos available on YouTube may be of poor quality. Health professionals should be aware that YouTube videos do not contain comprehensive, sufficient, up-to-date, and accurate information for patients.